Strategi Misi Orang Percaya dalam Mengaktualisasi Amanat Agung di Era New Normal - Joko Sembodo; Sari Saptorini (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
Church leaders and believers often focus too much on their respective churches and pay less attention to the unity of the body of Christ in winning souls. There is an understanding of the basic concept of evangelism that is not properly understood in its application as a witness of Christ. Becomes an obstacle in actualizing the mandate of the Great Commission. Through descriptive qualitative methods, it can be concluded that the essence of the Great Commission and its Challenges will lead believers to maintain the spirituality of believers because with a mature and spiritually mature spirituality they can become examples and role models so that they can actualize the Mission appropriately and in line with God's will. Furthermore, the believer has the knowledge that mission is a testimony of the believer's faith. hence this missiological concept carries the same spirit when Jesus wanted believers to be light and bring the news of salvation.AbstrakPemimpin gereja dan orang percaya tidak jarang terlalu lebih fokus pada gerejanya masing-masing dan kurang memberi perhatian pada kesatuan tubuh Kristus dalam memenangkan jiwa-jiwa. Adanya pengertian konsep dasar penginjilan yang tidak dimengerti secara benar dalam penerapannya sebagai saksi Kristus. Menjadi kendala dalam mengaktualisasi mandat Amanat Agung. Melalui metode kualitatif deskritif  dapat disimpulkan bahwa hakikat Amanat Agung  dan tantangannya akan membawa orang percaya  untuk menjaga  Spritualitas orang percaya sebab dengan kerohanian yang matang dan dewasa rohani dapat menjadi contoh dan teladan sehingga dapat mengaktualisasi Misi dengan tepat dan sejalan dengan kehendak Tuhan. Selanjutnya orang percaya memiliki pengetahuan bahwa misi sebagai kesaksian Iman orang percaya. maka konsep misiologi ini membawa semangat yang sama ketika Yesus menginginkan orang percaya menjadi terang dan membawa kabar keselamatan.